Painting the Picture – A Statistical Update on Women in Engineering in Australia - Marinelli, Melissa; Calais, Martina (2011)
The paper examines women's participation in engineering education and workforce in Australia. Using data from recent editions of Engineers Australia's The Engineering Profession: A Statistical Overview and drawing heavily on a detailed analysis of 2006 Population Census data, the aim is to show trends in the commencements, enrolments and graduations of female engineering students and to give an overview of the nature of female participation in the engineering workforce. Key findings include: slight increases in female percentage participation in engineering studies from 2001 to 2008, with growth in overseas and postgraduate students; the 2006 engineering labour force included 9.8% women, while 10.7% of individuals with engineering qualifications were women; unique and significant gender differences in the uptake of full-time and part-time employment exist; the gender pay gap is evident, with female engineers in full and part-time positions earning lower average weekly salaries than male engineers; a higher percentage of qualified engineering women are not in the labour force, compared to men, with a notable difference in the age groups around 35 years; and gender segregation of the engineering labour force by occupation and industry is seen, with a higher proportion of women in clerical / administrative and sales roles and health care and social and accommodation and food sectors. The work is the foundation for a regular update of gendered statistical data that will establish a detailed picture of engineering women in Australia and will assist with targeted progression of issues.